Taxonomic status of Allohoraeomorphus Franz (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2012)
Following the examination of the type material, the generic name Allohoraeomorphus Franz, 1986 is placed as a juniorobjective synonym of Horaeomorphus Schaufuss, 1889. The only species included in Allohoraeomorphus, Horaeomor-phus calcarifer (Franz, 1986), comb. n., is redescribed and its diagnostic characters, including the aedeagus and modified male metatrochanters are illustrated.